Differential modulation of the anterior cingulate and insular cortices on anxiogenic-like responses induced by empathy for pain - Benassi-Cezar, Giovana; Carmona, Isabela Miranda [UNESP]; Baptista-de-Souza, Daniela [UNESP]; Nunes-de-Souza, Ricardo Luiz [UNESP]; Canto-de-Souza, Azair [UNESP] (Elsevier, 2021)
Mice cohabiting with a conspecific in chronic pain display anxiogenesis in the elevated plus-maze (EPM). Given that the anterior cingulate (ACC) and insular (InC) cortices play a role in the modulation of anxiety, pain, and emotional contagion, we investigated (a) the FosB activation in both brain areas and (b) the effects of intra-ACC or -InC injection of cobalt chloride (CoCl2, a synaptic blocker), on the anxiety of mice cohabiting with a cagemate suffering pain. Twenty-one days after birth, male Swiss mice were housed in pairs for 14 days to establish familiarity. On the 14th day, mice were divided into two groups: cagemate sciatic nerve constriction (CNC; i.e., one animal of each pair was subjected to sciatic nerve constriction), and cagemate sham (CS; i.e., a similar procedure but without suffering nerve constriction). After that, both groups were housed again with the same pairs for the other 14 days. On the 28th day, mice had their brains removed for the immunoassays analyses (Exp. 1). For experiments 2 and 3, on the 23rd day, the cagemates received guide cannula implantation bilaterally in the ACC or InC and, on the 28th day, they received local injections of saline or CoCl2, and then were exposed to the EPM. Results showed that cohabitation with a conspecific with chronic pain decreases and increases neuronal activation (FosB) within the ACC and InC, respectively. Intra-ACC or InC injection of CoCl2 reversed the anxiogenic effect in those animals that cohabited with a conspecific in chronic pain. ACC and InC seem to modulate anxiety induced by emotional contagion in animals cohabitating with a conspecific suffering pain.
Keywords: Anterior cingulate cortex; Anxiety; Empathy; Insula; Mice